MOTIF SOSIAL DAN MOTIF PEKERJAAN GURU SLTP DI GUNUNGKIDUL - Siti Irene Astuti Dwiningrum (Universitas Negeri Yogyakarta, 2003)
Abstract This research is aimed at describing the profiles of social motif and work motif of the Junior Secondary School teachers in Gunungkidul, Yogyakarta. The population is the entire Junior Secondary School teachers in Gunungkidul Yogyakarta, whereas the sample is an intact class of training or 67 teachers, comprising 51 male and 16 female teachers. To reveal the profiles, three variables were measures namely: achievement motif, affection motif, and power motif. Five items on each variable were used to measure the social motif, and eight items of each variable was used to measure the work motif. The result shows that there is no gender difference in social as well as motif levels. Their profiles of the social motif and work motif are similar, namely: (1) the achievement motif is high (2) the affection motif is high, and (3) the power motif is moderate. Keywords: social motif, work motif, achievement, affection, and power